Carburization behavior at elevated temperatures and mechanical properties of a hot stamped complex phase steel - Risse, Jan Henning; Sippel, Frank; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2023)
As a lightweight construction strategy, hot stamped parts of ultra-high-strength steels with tailored properties are increasingly used for crash relevant components in car bodies, e.g., as B-pillars. With the process of tailored carburization, parts can be reinforced locally without increasing the sheet metal thickness. Thus, this process has the potential to be applied to lightweight components for no deformation zones, e.g., in the battery housings. Standardly, carburization is performed at 950 °C, with the highest strengths achieved at long times of up to 6 h, which prolongs the total process time. By raising the temperature, the carbon diffusion increases, which enables a reduced heat treatment time and, consequently, a shorter process time. Therefore, the objective of this study is to investigate the influence of elevated carburization temperatures on the mechanical properties of a carburized and hardened complex phase steel, CP-W® 800. A single carburization step at the enhanced temperatures leads to an embrittlement of the samples. Hence, an additional diffusion-annealing step is implemented to homogenize the carbon content, without enlarging the total heat treatment time. Depending on the time allocation of carburization and diffusion, the application of the diffusion annealing step results in higher strengths and ductility compared to only carburized samples.

Erweiterung des Prozessfensters für das lokale Aufkohlen bei erhöhten Temperaturen eines pressgehärteten Komplexphasenstahls - Risse, Jan Henning; Merklein, Marion (Warmumformung von höchstfesten Vergütungsstählen: Tagungsband zum 18. Erlanger Workshop Warmblechumformung, 2023)
Als Leichtbaustrategie werden in der Automobilkarosserie, z. B. als B-Säulen, höchstfeste Stähle mit maßgeschneiderten Eigenschaften zunehmend für crashrelevante Bauteile eingesetzt. Mit dem Verfahren Tailored Carburization können Bauteile lokal verstärkt werden, ohne die Blechdicke zu erhöhen und ohne die Notwendigkeit von komplexer Werkzeugtechnik. Damit hat dieses Verfahren das Potenzial, bei Leichtbauteilen mit verformungsfreien Zonen, z.B. bei Batteriegehäusen, oder in Kleinserien Verwendung zu finden. Normalerweise wird die Aufkohlung bei 950 °C durchgeführt, wobei die höchsten Festigkeiten bei langen Zeiten von bis zu 6 Stunden erreicht werden, was die Gesamtprozesszeit verlängert. Durch die Erhöhung der Temperatur nimmt die Kohlenstoffdiffusion zu, was eine kürzere Wärmebehandlungszeit und folglich eine kürzere Prozessdauer ermöglicht, wie bereits grundlegend gezeigt wurde. Ziel dieser Untersuchung ist es daher, den Einfluss der einzelnen Aufkohlungsparameter beim Diffusionshärten auf die mechanischen Eigenschaften des aufgekohlten und gehärteten Komplexphasenstahls CP-W® 800 zu identifizieren sowie das Prozessfensters zu erweitern.<br
Keywords: Presshärten; Maßgeschneiderte Eigenschaften; Aufkohlung

Investigation of the Thermomechanical Properties During Hot Stamping of a Complex Phase Steel Carburized at Elevated Temperatures - Risse, Jan Henning; Merklein, Marion (Hot Sheet Metal Forming of High-Performance Steel, 2024)
In order to reduce greenhouse gas emissions or to increase the range of electrically powered vehicles, several lightweighting strategies are applied in the manufacturing of the latest cars. The hot stamping of ultrahigh-strength steels, which is becoming an increasingly common strategy, can be used to produce lighter components with reduced sheet thickness. In particular, parts with tailored properties that are already in use for B pillars for example, increase the crashworthiness and the lightweight potential at the same time. In contrast to existing processes, tailored carburization does not require complex tooling or intricate furnace technologies, material thickening, or welding processes to locally adjust the mechanical properties. The to-be-reinforced areas are geometrically flexible, which makes this process especially suitable for small batch series of lightweight components. At standardly 950 °C, the carburization takes up to 6 h to achieve the highest combination of strength and ductility. Thus, strategies are needed to shorten the total process time. Diffusion hardening at elevated temperatures seems promising to achieve a similar level of mechanical properties but in a significantly reduced time. So, this contribution aims to investigate the dependence of the thermomechanical behavior on the carburization above 950 °C, forming temperature, and strain rate of a tailored carburized material. Therefore, thermal tensile tests were performed with the complex phase steel CP-W® 800 in two different carburized states as well as in the not-carburized state. In the physical simulator Gleeble 3500 GTC the specimens pass through a simulated hot stamping process and are tested at different forming temperatures with varying strain rates. In addition to the dependency analysis, the obtained flow curves can also be used to partially generate a thermo-mechanically coupled simulation. This model is intended to replicate the hot stamping of components with customized properties induced by tailored carburization.<br

Stability of Bipolar Plate Materials for Proton-Exchange Membrane Water Electrolyzers: Dissolution of Titanium and Stainless Steel in DI Water and Highly Diluted Acid - Fiedler, Lena; Ma, Tien Ching; Fritsch, Birk; Risse, Jan Henning; Lechner, Michael; Dworschak, Dominik; Merklein, Marion; Mayrhofer, Karl; Hutzler, Andreas (ChemElectroChem, 2023)
The widespread use of proton exchange membrane water electrolyzers (PEMWE) is hindered by their high cost, of which a colossal factor is caused by the bipolar plates (BPP). In this paper, we investigate the stability of two BPP materials on-line with an optimized scanning flow cell setup coupled to an inductively coupled plasma mass spectrometer (SFC-ICP-MS), as well as scanning electron microscopy (SEM). The stability of currently used titanium and a cheaper alternative, stainless steel (SS) 316L, were characterized in deionized (DI) water and 0.5 mM H2SO4 to mimic the conditions at the BPP under operation. We show that the dissolution of Ti is negligible, whereas SS 316L degrades notably. Here, besides pH, the applied potentials play a crucial role. Nonetheless, even for the highest measured dissolution rate of SS 316L, the contamination in a full cell is estimated to remain below 1 ppm. This work illustrates the capabilities of on-line high-throughput stability tests for BPP materials and could therefore contribute towards optimization of cost-effective PEMWE.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Cyclic voltammetry; Stability; Stainless Steel; Titanium; Water splitting

The ESAFORM benchmark 2023: interlaboratory comparison benchmark for the characterization of microstructural grain growth and dynamic recrystallization kinetics of a single-phase Ni-base superalloy - Agirre, Julen; Bernal, Daniel; Flipon, Baptiste; Bernacki, Marc; Brüggemann, Holger; Bailly, David; Merklein, Marion; Hagenah, Hinnerk; Risse, Jan Henning; Madej, Łukasz; Muszka, Krzysztof; Cichocki, Kamil; et al. (International Journal of Material Forming, 2025)
This paper presents an extensive benchmark study conducted across eight European research centres, focusing on the high-temperature testing of the Alloy 625 nickel-based superalloy to evaluate its flow behaviour and microstructural evolution, including grain growth (GG) and dynamic recrystallization (DRX). Uniaxial compression tests were performed at 1050 °C and three strain rates (0.1 s⁻1, 1 s⁻1, and 10 s⁻1) using six testing facilities categorised into three types: two conventional thermomechanical machines equipped with electrical resistance furnaces, two deformation dilatometers with induction heating, and two Gleeble machines with Joule heating. Flow curves were compared, and EBSD analysis was conducted to examine DRX. Virtual twins of tests were developed to estimate the thermomechanical history at the centre of the samples, where microstructural observations were conducted. The study methodically discussed the variability in thermomechanical behaviour and DRX results. Additionally, GG was investigated through heat treatments at 1150ºC for various hold times, using the three heating methods mentioned. Significant effects of the heating methods on GG were identified. In-situ synchrotron analysis at PETRA III DESY provided deeper insights into microstructural evolution. Considering the extensive findings of this research, this paper aims to establish guidelines and define best practices for high-temperature testing to characterise the thermomechanical behaviour and microstructural evolution of materials, while providing insights for advancing experimental mechanics and optimising constitutive model development.
Created from Fastlane, Scopus look-up
Keywords: Benchmark; High temperature testing; Uniaxial compression; Microstructural evolution; Grain growth; Dynamic recrystallization; EBSD analysis; Virtual twins; In-situ testing